Análise da dinâmica da arrecadação do ISSQN no município de Fortaleza - Pereira, Diogo de Matos (2017)
The study investigates the dynamics of the collection of the Imposto sobre Serviços de Qualquer Natureza(ISSQN) [Tax on Services of any Nature]in Fortaleza, usingan autoregressive model with endogenous limit value following the proposal of Caner and Hansen (2001). Monthly data for this tax, aggregated and in selected segments of sectors considered as being “essential goods”and “luxury goods”, from January 2012 toMay 2017,adjusted by the IPCA,were used in the modeling, the estimates allowed to infer that: i) The total collection, in real terms, follows a non-linear and globally explosive dynamics, as well as in the segment of Gyms where only for variations belowR$ 7,500, the trend is stationary; ii) The Buffets sector did not show a regime change and has a globallystationary dynamics; iii) The School segment has a similar behavior to the total revenue; iv) The University sector presents a linear and globally explosive dynamics; vi) The Accommodation and Graphic Services segments have a similar dynamic, having a non-linear behavior and a globally stationary trend. Together, the results allow to infer that the evolution of the ISSQN of Fortaleza, in an aggregated way and in real terms, brings optimistic perspectives regarding the resumption of growth of the local economy,even though in some segments of suppliers of "luxury goods" like Buffets and Accommodations, as well asothers with relevant seasonal effect, such as Gyms and Graphic Services, the inertia for a potential recovery still persists.